1996
DOI: 10.1021/jm960230h
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic Activity of a Series of α-Alkylthio and α-Alkoxy Carboxylic Acids Related to Ciglitazone

Abstract: The thiazolidinedione moiety of ciglitazone and its analogues can be replaced by an alpha-alkoxy or alpha-thioether carboxylic acid group. The influence of the nature of the R group, the length of the connector to the aromatic backbone of the molecule, and the stereochemistry have been studied. The most potent compounds have glucose-lowering activity at doses as low as 0.01 mg/kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…[15][16][17] There are a number of groups that endeavor to produce new antidiabetic agents in this area. [18][19][20][21][22][23][24][25][26][27][28][29] Although the mechanisms of insulin resistance and action of 2,4-thiazolidinedione analogs and related compounds are not yet fully understood, a number of reports suggest that pioglitazone reduces insulin resistance. For example, treatment with pioglitazone increased the insulin action for the decrease of hepatic glucose production and for the increase of peripheral glucose utilization in Wistar fatty rats.…”
mentioning
confidence: 99%
“…[15][16][17] There are a number of groups that endeavor to produce new antidiabetic agents in this area. [18][19][20][21][22][23][24][25][26][27][28][29] Although the mechanisms of insulin resistance and action of 2,4-thiazolidinedione analogs and related compounds are not yet fully understood, a number of reports suggest that pioglitazone reduces insulin resistance. For example, treatment with pioglitazone increased the insulin action for the decrease of hepatic glucose production and for the increase of peripheral glucose utilization in Wistar fatty rats.…”
mentioning
confidence: 99%
“…The analytical data of the synthesized oxyiminoacetic acids (7,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) are shown in Table 1.…”
Section: Chemistrymentioning
confidence: 99%
“…Many companies are still endeavoring to find a new glucose lowering agent. [23][24][25][26][27][28][29][30][31][32][33][34][35] Although the precise mechanism of action of these drugs remains unknown, recent study suggests that antidiabetic thiazolidinediones interact with a family of nuclear receptors known as peroxisome proliferator-activated receptor (PPAR)-g. 36) PPARg is one of a subfamily of PPARs encoded by independent genes. Three human PPARs, designated PPARa, PPARg, and PPARd, have been identified to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1), which was designed based on the structure of rosiglitazone and 15d-PGJ 2 , 12,13) as a potent PPARg ligand. 14) To find more potent PPARg agonists and novel PPARa agonists, we chose compound 1 as the lead structure, because recent reports indicated that PPARg affinity can be increased by the introduction of substituents into the C-2 position of propanoic acid, [15][16][17][18][19] and minor structural modifications can convert PPAR subtype selectivity. [20][21][22] In this article, we report the synthesis, binding affinity and biological activity of PPAR ligands based on the structure of compound 1.…”
mentioning
confidence: 99%